Vinylidenedithiophenmethyleneoxindole: a centrosymmetric building block for donor–acceptor copolymers. Issue 7 (14th January 2016) - Zhang, Weifeng; Zheng, Naihang; Wei, Congyuan; Huang, Jianyao; Gao, Dong; Shi, Keli; Xu, Jie; Yan, Donghang; Han, Yanchun; Yu, Gui
Abstract : A novel building block (VDTOI) was designed and synthesized. VDTOI-based copolymers exhibit a high mobility of 0.35 cm 2 V −1 s −1 . Abstract : Further development of new building blocks is crucial for realizing next-generation, high-performance organic semiconducting materials. In the paper, the design and synthesis of a novel π-extended analogue of isoindigo, vinylidenedithiophenmethyleneoxindole (VDTOI ), and twoVDTOI -based copolymers is reported. The centrosymmetricVDTOI unit possesses a special acceptor–donor–acceptor structure and contains a highly planar conjugated backbone because of the presence of S⋯O conformational locks. Of special importance is the fact that theVDTOI unit has the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital and energy levels of −5.35 eV/−3.42 eV, which are similar properties to those of the thiophene-flanked diketopyrrolopyrrole building block. The previously mentioned structural features indicate thatVDTOI might be a potential building block for constructing polymeric semiconductors. As a trial, twoVDTOI -based copolymers were synthesized, namelyP1 andP2 . The two copolymers show good thermal stability and broad absorption spectra ranging from 330 to 740 nm. Their HOMO energy levels of around −5.40 eV match well with the work function (5.13 eV) of a gold (Au) electrode, which is indicative of effective hole injections from the Au electrodes to polymer semiconductor films. Both theP1 - andP2 -based field-effect transistors exhibited typical p-type transport characteristics. The highest mobility of 0.35 cm 2 V −1 s −1 was achieved inP1 -based devices.